Effect of immunomodulators on biochemical attributes of cows with Endometritis - SAHADEV, A; DEVARAJ, M; HONNAPPA, T G; MURTHY, V CHANDRASHEKARA (The Indian Journal of Animal Reproduction, 2007)
Concentration of certain serum biochemical constituents and pH of uterine flushings in 84 crossbred dairy cows were studied. Six groups with 12 cows in each group received either I) LPS from E.coli, 100 μg, 2) Oyster glycogen, 500 mg, 3) Autologus plasma (AP), 30 ml, 4) LPS 100 μg plus AP IO ml, 5) Antibiotic (based on ABST) or 6) Phosphate buffer saline 30 ml (Control) intrauterine. Mean total serum protein, albumin, globulin, albumin/globulin ratio, alkaline phosphatase and serum urea nitrogen did not vary significantly (P:::,0.05) after 24 hours of treatment. The mean pH decreased significantly (P:::,0.05) in all the treated groups compared to its initial level. It was concluded that estimation of these serum biochemical parameters may not be tool for diagnosis of endometritis but pH would certainly help.